Study of Bipedal Robot Walking Motion in Low Gravity: Investigation and Analysis. (2nd September 2014) - Omer, Aiman; Hashimoto, Kenji; Lim, Hun-Ok; Takanishi, Atsuo
Humanoid robots are expected to play a major role in the future of space and planetary exploration. Humanoid robot features could have many advantages, such as interacting with astronauts and the ability to perform human tasks. However, the challenge of developing such a robot is quite high due to many difficulties. One of the main difficulties is the difference in gravity. Most researchers in the field of bipedal locomotion have not paid much attention to the effect of gravity. Gravity is an important parameter in generating a bipedal locomotion trajectory. This research investigates the effect of gravity on bipedal walking motion. It focuses on low gravity, since most of the known planets and moons have lower gravity than earth. Further study is conducted on a full humanoid robot model walking subject to the moon's gravity, and an approach for dealing with moon gravity is proposed in this paper.